Feasibility, validity and utility of HIV testing data as key components of HIV case-based surveillance - Jacob, Nisha (Department of Public Health and Family Medicine, 2025)
Background: HIV case-based surveillance (CBS) is recommended by the World Health Organization and other global agencies, for tracking progress towards achieving the 95-95-95 targets to end the HIV epidemic. CBS involves gathering individual-level data for each person diagnosed and linking these data from multiple data sources to other key data points along the HIV care cascade. Despite the high burden of HIV in sub-Saharan Africa and existing routine HIV program monitoring, opportunities to implement CBS have not been optimally used. The maturation of the health information system in the Western Cape province presents a unique opportunity to implement a version of case-based HIV surveillance that is integrated into a routine operation system within the antenatal services setting. This thesis seeks to explore the validity of HIV case ascertainment within a routine health information exchange, the feasibility of embedding HIV testing data into routine information systems and the utility of these routine data for enhanced HIV CBS. Methods: Routine pregnancy and HIV data consolidated within the Provincial Health Data Centre (PHDC) from January 2010 to December 2020 were analysed using retrospective cohort and cross-sectional methods. Routine data were linked using a unique patient identifier to ascertain sentinel events within the HIV and vertical transmission prevention cascades. Temporal trends in HIV prevalence, HIV testing, linkage to care, ART coverage and vertical transmission estimates were evaluated and where relevant, triangulated with other key data sources historically used as sources for these estimates. These included routine aggregate data from the District Health Information System, national and provincial sentinel antenatal seroprevalence surveys and mathematical model estimates. Risk factors for vertical transmission were further evaluated using multivariable analyses. A specific intervention implemented at a selected facility to enhance CBS through digitisation of routine point-of-care HIV tests was further evaluated for operational feasibility using both quantitative and qualitative research methods. Findings: PHDC antenatal HIV prevalence estimates from 2011-2013 were widely disparate from aggregate and survey data (due to incomplete electronic data), whereas from 2014 onwards,n estimates were within the 95% confidence interval of survey estimates, and closely correlated to aggregate data estimates (r=0.8; p=0.01). PHDC data show a slow but steady increase in provincial antenatal HIV prevalence from 16.7% in 2015 to 18.6% in 2020. ART coverage by the time of delivery in mothers of live births increased from 67.4% in 2011 to 94.7% by 2019. This pattern of increasing antenatal ART coverage was also seen in the DHIS data, and estimated by mathematical models, but was less consistent in the antenatal survey data. Ascertainment of HIV status among children exposed to HIV increased over time to 87.2% (16 908/19 382) in 2020. In recent years (2017 – 2020), 2.0% of children exposed to HIV (1 461/73 590) were diagnosed with HIV. Children born after implementation of lifelong ART in pregnant women, were less likely to have HIV than children born in the prior policy period (aOR 0.7; 95% CI 0.6 – 0.7), mediated through expanded ART access. Young maternal age, no antenatal ART, previous TB diagnosis and no records of antenatal visits were associated with vertical transmission. The intervention to enhance CBS through digitisation of HIV testing data, demonstrated that 51.3% (95% CI 48.4–54.1%) of patients testing HIV-positive at a selected health facility were retesting, supporting the utility of these data to enhance CBS. While the intervention is operationally feasible, various logistical, health system and cost-related challenges require careful consideration before scale-up. Conclusions:This study demonstrates that CBS embedded within a routine health information exchange may be reliably used for HIV prevalence, ART coverage and vertical transmission surveillance, providing more granular estimates, more efficiently than sentinel surveillance and aggregate programmatic data. This would enable more timely action in response to surveillance such as interventions targeting gaps in care or tailored for high-risk groups. However, these strategic gains may be strengthened by digitisation of HIV point-of-care data, implementation of which is operationally feasible but complex.